2021
DOI: 10.35942/ijcfa.v3i1.168
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Structure and Financial Performance of Companies Listed at the Nairobi Securities Exchange, Kenya

Abstract: Performance of firms is predominantly contingent on the deliberate decisions cautiously made and executed by the owners therefore a linkage exists between ownership structure and performance financially. Owners are part of a segment that makes decisions by the virtue of their relationship with the firm. Therefore, the question of what maybe the most efficient ownership structure is relevant. Through the period 2014 to 2018, there was an increase in the listed firms that issued profit warnings with others like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…K. Morck et al (2000), Hart (1995), Mehran (1995), Jensen (1993) who reported positive and significant influence of board ownership on financial performance. Also in tandem with the findings of Alshouha et al (2021), Tayachi et al (2021), Alabdullah (2018), Shleifer and Vishny (1997), Vu et al (2018), Nyaguthii et al (2019), Bhagat and Bolton (2013), Z. Chen et al (2005), Demsetz and Villalonga (2001), R.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…K. Morck et al (2000), Hart (1995), Mehran (1995), Jensen (1993) who reported positive and significant influence of board ownership on financial performance. Also in tandem with the findings of Alshouha et al (2021), Tayachi et al (2021), Alabdullah (2018), Shleifer and Vishny (1997), Vu et al (2018), Nyaguthii et al (2019), Bhagat and Bolton (2013), Z. Chen et al (2005), Demsetz and Villalonga (2001), R.…”
Section: Resultssupporting
confidence: 80%
“…The common notion is that managers will work for the best interests of organizations when they have ownership in the firm and vice versa (Alabdullah, 2018; Shleifer & Vishny, 1997). Thus, an increase in the proportion of shares owned by the managers may help to align the interest of managers and shareholders by restricting them not to waste the firm’s resources for their own well-being (Nyaguthii et al, 2019; Vu et al, 2018). Agency problem may be reduced if managers hold large fraction of the firm’s equity.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation